Gregory S. Ezra A Festschrift from Theoretical Chemistry Accounts - Keshavamurthy, Srihari (Springer, 2015)
In this Festschrift dedicated to the 60th birthday of Gregory S. Ezra, selected researchers in theoretical chemistry present research highlights on major developments in the field. Originally published in the journal Theoretical Chemistry Accounts, these outstanding contributions are now available in a hardcover print format, as well as a special electronic edition. This volume provides valuable content for all researchers in theoretical chemistry and will especially benefit those research groups and libraries with limited access to the journal.